Achieving high joule heating and self-cleaning performance in copper-coated fabrics with excellent microwave shielding - Luo, Cheng-Long; Huang, Ming-Lu; Sun, Chang; Zhao, Kun-Yan; Hu, Zongqian; Wang, Ming (Cellulose (London), 2023)
Herein, non-woven cotton fabrics (NWCFs) with excellent microwave shielding, Joule heating and self-cleaning performance were achieved by modifying NWCFs with dopamine, then depositing a thin copper (Cu) layer, and finally coating with a thin polydimethylsiloxane (PDMS) layer. Because of the high conductivity of Cu layer and unique heterogeneous structure, the electrical conductivity of 22,548 S/m and electromagnetic interference shielding effectiveness (EMI SE) of ~ 110 dB were obtained in the surface modified NWCFs under 25 mM copper plating solution. Furthermore, the composite fabrics have excellent Joule heating performance, which can reach 43 °C in 15 s at a voltage of 0.5 V even after 1000 bends. In addition, the composite fabrics also have outstanding super-hydrophobic properties, which can protect against a variety of common solutions and achieve self-cleaning. This study provides a simple strategy to prepare excellent Joule heating and electromagnetic interference shielding and self-cleaning cotton fabrics. Graphic Abstract